Beyond Inclusion: Surakarta Special Education Teachers' Perspectives on Humanistic Pedagogy in the Era of Standardization - Nimas Ayu Nawal Maulida; M. Thoyibi; Abdillah Nugroho (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This qualitative study explores how special education teachers (SLB) in Surakarta negotiate humanistic and personalized pedagogical approaches within increasingly standardized educational systems. Drawing on critical pedagogy theory and inclusive education frameworks, this research examines the tensions between transformative, student-centered pedagogical ideals (such as those popularized in cultural narratives like Freedom Writers) and the structural, administrative, and resource constraints faced by SLB teachers working with students with diverse disabilities. Through semi-structured interviews with five special education teachers from public SLB institutions in Surakarta, this study investigates how educators conceptualize authentic connection, individualized attention, and transformative learning for students with intellectual, sensory, and physical disabilities who often face compounded marginalization due to poverty and social stigma. The findings reveal significant gaps between pedagogical ideals and practical realities, including excessive administrative burdens, inadequate funding for adaptive materials, high student-teacher ratios, outcome-driven assessment pressures, and limited emotional support systems for teachers. This study argues that while humanistic education promises to transform marginalized students' lives, systemic barriers in Indonesian special education prevent teachers from fully realizing this vision. This research contributes to ongoing debates about inclusive education in developing contexts and offers implications for reimagining special education policy that prioritises teacher capacity, student dignity, and authentic learning over bureaucratic compliance.